Which of the following is the general form of the equation 5x 2 - 20x = 15?
x 2 - 4x = 3
x 2 - 4x - 3 = 0
5x 2 - 20x - 15 = 0

x^2 - 4x - 3 = 0

Expert answered|badgerpoe|Points 690|

Question

Asked 7/12/2011 7:29:22 PM

Updated 7/13/2011 2:02:48 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

The volume of a rectangular prism is equal to x3 + 4x2 + 3x.
What is the longest edge of the prism?
**Weegy:** Yes they are equal. The reason is anything to the power of zero equals zero. (More)

Question

Expert Answered

Asked 7/12/2011 1:47:45 PM

0 Answers/Comments

Factor completely. x^2-10x+24 **Weegy:** (x-6)(x-4) (More)

Question

Expert Answered

Asked 7/12/2011 1:41:06 PM

0 Answers/Comments

The volume of a rectangular prism is equal to x^3 + 4x^2 + 3x.
What is the longest edge of the prism?
**Weegy:** 3x + 2y = 11, y = 4x --> 3x + 2(4x) = 11 --> 3x + 8x = 11 --> x = 11/11 = 1 **User:** Factor the four-term polynomial.
mn - 15 + 3m - 5n
(More)

Question

Expert Answered

Asked 7/12/2011 1:55:20 PM

0 Answers/Comments

Factor the four-term polynomial.
mn - 15 + 3m - 5n
**Weegy:** mn-15+3m-5n
Let's rearrange the terms
mn+3m - 15-5n
= m*(n + 3) - 5(n+3)
= (n+3)*(m-5) **User:** Factor completely.
49t^6 - 4k^8
**Weegy:** (7t³ + 2k^4)(7t³ - 2k^4) (More)

Question

Expert Answered

Asked 7/12/2011 2:00:17 PM

0 Answers/Comments

Factor completely.
49t^6 - 4k^8

Question

Not Answered

Updated 286 days ago|6/16/2014 11:11:27 AM

1 Answer/Comment

49t^6 - 4k^8 = -(2 k^4-7 t^3) (2 k^4+7 t^3)

Added 286 days ago|6/16/2014 11:11:27 AM

This answer has been confirmed as correct, not copied, and helpful.

20,164,857 questions answered

There are no comments.